2018
DOI: 10.20473/bhsj.v1i1.8210
|View full text |Cite
|
Sign up to set email alerts
|

Age as the Risk Factor that Affected the Increased Degree of Uterine Prolapse

Abstract: Introduction: Uterine prolapse is a gynecological problem that women often experience with a prevalence of 50% and is predicted that the next 30 years will increase by 45% as life expectancy increases. Increased degrees of uterine prolapse have an impact on the deterioration of women's quality of life. The uterine prolapse is influenced by several mutually supportive factors. The purpose of this study was to analyze the relationship between these factors to the degree of uterine prolapse.Methods: This research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 12 publications
0
11
0
4
Order By: Relevance
“…These results were similar to another study which found that older age and menopause are risk factors for uterine prolapse. 12,13 This study found that the majority of uterine prolapse occurred in grande-multiparous. This condition is closely related to pregnancy and childbirth.…”
Section: Discussionmentioning
confidence: 85%
“…These results were similar to another study which found that older age and menopause are risk factors for uterine prolapse. 12,13 This study found that the majority of uterine prolapse occurred in grande-multiparous. This condition is closely related to pregnancy and childbirth.…”
Section: Discussionmentioning
confidence: 85%
“…Selain itu, di Poliklinik Ginekologi RSUD Dr. Soetomo dari tahun 2007 -2011 , angka kejadian prolapsus uteri cukup tinggi dan merupakan kasus POP terbanyak yaitu 66,30%. 16 Diperkirakan selama 30 tahun ke depan, permintaan pengobatan POP akan meningkat 45%, sejalan dengan peningkatan populasi wanita berusia di atas 50 tahun. 6…”
Section: Angka Kejadianunclassified
“…5 Shervil dalam studinya menyimpulkan bahwa usia merupakan faktor risiko utama yang memengaruhi derajat prolaps uteri yang dikarenakan melemahnya jaringan dasar panggul dan otot pada wanita yang telah lanjut usia. 16…”
Section: Usiaunclassified
“…Menurut penelitian oleh The Women's Health Initiative(WHI), kejadian POP di Amerika Serikat adalah 41% wanita berusia 50-79 tahun dan prolapsus uteri menempati urutan ketiga (14% pasien dengan POP). 16 Prolaps organ panggul hampir ditemukan pada semua wanita yang telah melahirkan, tapi hanya 5-20% yang bergejala. 14 Chang dan Sultana dalam studinya menyebutkan bahwa wanita Asia memiliki tingkat prolaps organ panggul yang lebih tinggi daripada wanita dalam kelompok ras lain yatu 67%.…”
Section: Angka Kejadianunclassified